Tao Weberna (und Heidegger ist auch dabei) - Trzęsiok, Marcin (Res Facta Nova, 2025)
The music and aesthetics of Anton Webern, in spite of their seemingly radical innovativeness, are rooted in the culture of German romanticism. It is thus not surprising that in relation to this work one could conduct the same thought experiment that German Sinologists applied to romantic poetry – to find in Webern’s work a whole sequence of analogies with the Chinese world view and aesthetics. This essay considers a number of such convergences: connection to nature understood as an infinite series of transformations, the role of silence and “lingering tone”, distrust of civilisation and cultivation of the ideal of archaic simplicity, inner harmony understood as a balance of opposites, the motif of longing, elitism and, finally, twelve-tone row s an analogy to Tao.